3PC-026 What is the best chemical decontamination solution for conventional anti-neoplastic drugs in a hospital compounding unit?. (March 2019) - Simon, N; Odou, P; Decaudin, B; Bonnabry, P; Fleury-Souverain, S
Abstract : Background: Several decontamination methods are currently available to reduce the occupational exposure of hospital facilities to conventional anti-neoplastic drugs. Alcohol-based microbicides are not sufficiently efficient in removing chemical contamination and data are lacking on many marketed biocides. Recent data confirm that using a specific chemical decontamination solution is helpful in removing traces of contaminants. Purpose: To perform a literature review in order to help pharmacists in choosing a chemical decontamination solution to implement in their compounding unit. Material and methods: Articles were searched on Pubmed using the following requests: 'antineoplastic agents AND cleaning' or 'antineoplastic agents AND chemical degradation' or 'antineoplastic agents AND chemical decontamination'. Criteria used to classify the performance and usability of decontamination solutions were: decontamination efficiency, number and nature of tested contaminants, hazardousness of the decontamination solution, implementation difficulties and respect of the aseptic environment. Results: Two-hundred and seventy-four articles were retrieved following the request application. Two-hundred and fifty-seven articles were discarded for different reasons leading to the analysis of 17 articles. Fifty-nine methods were tested as degradation (n=19) or desorption methods (n=40) with various decontamination efficiencies ranging from ≤10% to 100%. Applying the selection criteria, three decontamination solutions were chosen: sodium hypochlorite, admixture of 10 -2 M sodium dodecyl sulfate (SDS) and 70% isopropanol (80/20), marketed two steps towelettes kit (1. Quaternary ammonium solution, 2. Isopropanol). Their inertness to facilities' surfaces is different and sodium hypochlorite solutions oxide metals. Solutions involving tension-active agents such as SDS may form a film on the facilities surface, which may alter the sterility environment. Conclusion: The applied selection criteria led to select only three decontamination solutions. Their application modalities are also to be discussed regarding the biological and chemical facilities' monitoring. As the solutions were assessed with various methodologies, further studies are necessary to compare them in the same conditions. Because each solution has been tested with different contaminants, new studies are required to confirm their ability to decontaminate other conventional anti-neoplastic drugs. References and/or acknowledgements: Vasseur, et al. EJHP 2017;24(Suppl 1):A218. doi:10.1136/ejhpharm-2017–000640.485 Vasseur, et al. PLos One 2018. No conflict of interest.